2014
DOI: 10.1177/2325957414539197
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Pharmacy-Based Adherence Measurement in Predicting Virologic Outcomes in an Adult HIV-Infected Cohort in Jos, North Central Nigeria

Abstract: Adherence to drug refill is a useful predictor of successful virologic control and could be utilized for routine monitoring of adherence to cART in our clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The methods used to assess adherence in our studies were previously validated and shown to reliably measure ART adherence in other studies [ 7 , 21 23 ]. In fact, it has been shown that regular attendance to pharmacy refills and clinic visit appointments is associated with retention in care and better adherence to ART [ 36 ], predicts viral suppression, and that sub-optimal attendance predicts virologic failure [ 9 , 10 , 21 , 23 , 37 ] and drug resistance [ 15 ]. In our study, a subject was considered non-adherent for a refill if he/she had missed pharmacy refill for over 48 hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods used to assess adherence in our studies were previously validated and shown to reliably measure ART adherence in other studies [ 7 , 21 23 ]. In fact, it has been shown that regular attendance to pharmacy refills and clinic visit appointments is associated with retention in care and better adherence to ART [ 36 ], predicts viral suppression, and that sub-optimal attendance predicts virologic failure [ 9 , 10 , 21 , 23 , 37 ] and drug resistance [ 15 ]. In our study, a subject was considered non-adherent for a refill if he/she had missed pharmacy refill for over 48 hours.…”
Section: Discussionmentioning
confidence: 99%
“…The adult AIDS Clinical Trial Group (ACTG) adherence questionnaire [ 16 ] was translated into French and validated through back-translation [ 17 ]. This ART adherence questionnaire has been validated in population studies in both developed [ 18 20 ] and resources limited countries [ 20 23 ], and we previously adapted and validated this French version of the ACTG questionnaire in Cameroon [ 17 ]. This questionnaire was administered to each subject by a physician (JYF) in a face-to-face interview, and the same physician recorded all interview results.…”
Section: Methodsmentioning
confidence: 99%
“…Patients who were less than 95% consistent in their drug refill were considered non adherent to therapy, while those who were 95% and above consistent in drug refill were classified as adherent. 14 A research specific pharmacy intervention documentation form adapted from literature 15 was used for documentation of intervention carried out at each patient pharmacy visit. The form also captured information on patient demographics, actions taken, recommendations made, acceptance rate of recommendations, time taken for intervention and perceived patient benefits.…”
Section: Methodsmentioning
confidence: 99%
“…[19] Although, our analysis did not adjust for the biological variables like CD4+ cell count or HIV viral load, we know that most of the HIV infected women in our sample have been on successful antiretroviral therapy supported by the Presidential Emergency Plan For AIDS Relieve (PEPFAR) adult HIV treatment program in Jos. [20][21][22][23] This assumption is supported by follow-up data in a US population that did not nd a signi cant difference in incident cervical dysplasia and cancer in HIV population on successful HAART. [24,25] Also, recent data from the United Nations on AIDS (UNAIDS) showed that over 80% of HIV infected adults on antiretroviral treatment in Nigeria had HIV viral loads that were suppressed.…”
Section: Discussionmentioning
confidence: 93%